Chilling Journalism: Can Newsgathering be Harassment or Stalking?. Issue 1 (2nd January 2017) - Coyle, Erin; Robinson, Eric
Abstract : Newsgathering often requires journalists to ask uncomfortable questions or make multiple attempts to talk to unwilling sources. Some journalists have been accused of harassment, even when the plain language of state laws would not classify their actions as criminal conduct. In the rare instances that journalists actually were charged with harassment or subject to protective orders for stalking, district attorneys or judges typically did not allow them to be punished. This study, however, found nine statutes that might be applied to punish newsgathering activities that are neither hounding nor harassing. It also identifies language from statutes that clearly could not be applied to punish newsgathering communications by journalists. The article recommends that prosecutors and judges continue to prevent the application of criminal harassment and stalking laws to newsgathering activities.